Investigating the Efficiency of Ghanaian banks before and after the minimum capital requirement increase - Obeng, Rosina (2013)
Using SFA and a two-stage approach, this dissertation investigates the short-term impact of the recent increase in the minimum capital requirement on the cost and profit efficiency of Ghanaian banks over the period 2007-2012. The efficiency score obtained from the first stage are then utilized in the second stage to evaluate the determinants of Ghanaian bank efficiency.